Vous êtes sur la page 1sur 6

ME235A Finite Element Anlysis

Fall, 2001
Solution to Problem Set #3
Oct. 24 2001
Exercise 2 (page 46) (The problem is not restated.)
i. The variational equation is
a( w h , u h ) + ( w h , u h ) = ( w h , f ) + w h (0)h
Let u h = v h + g h , then,
a( w h , v h ) + ( w h , v h ) = ( w h , f ) + w h (0)h a ( w h , g h ) ( w, g h )
n

ii. Let w h = c A N A and v h = d A N A

A =1

A =1
n

a ( c A N A , d B N B ) + ( c A N A , d B N B )
A =1

B =1

A =1

B =1

A =1

A =1

A =1

= ( c A N A , f ) + c A N A (0)h a ( c A N A , g h ) ( c A N A , g h )

c d (a( N
n

A =1

B =1

, N B ) + ( N A , N B ) ) = c A ( N A , f ) + N A (0)h a( N A , g h ) ( N A , g h )
A=1

This can be written as

A =1

K
B =1

AB

d B = FA

A = 1, , n

where K AB = a ( N A , N B ) + ( N A , N B ) .
e
The element stiffness matrix k e = k ab
is given as

[ ]

e
k ab
= a ( N a , N b ) e + ( N a , N 2 ) e

iii.

+1

+1

e
k ab
= N a , ( ) N b , ( )( x , ( )) 1 d + N a ( ) N b ( ) x , ( )d

1 h e
+
1 1 1 h e 2 1 h e
3
+
=
ke = e

1 2
1

he
1
1

6
h

+
h e
6
iv.

1 h e
e +

6
h
1 h e
+
3
he

K AB = a ( N A , N B ) + ( N A , N B ) = a ( N A , N B ) + ( N A , N B )
= a ( N B , N A ) + ( N B , N A ) = a ( N B , N A ) + ( N B , N A ) = K BA

v. Let c = {cA}, A = 1, , n. Use the components of c to construct a vector wh in Vh.

n

wh = cA N A
A =1

c T Kc =

c A K AB c B =

A, B =1

c [a( N

A, B =1

, N B ) + ( N A , N N )] c B

ME235A Finite Element Anlysis

Fall, 2001
n

A =1

B =1

A =1

B =1

= a ( c A N A , c B N B ) + ( c A N A , c B N B ) = a ( w h , w h ) + ( w h , w h )
1

= ( w,hx ) 2 dx + ( w h ) 2 dx 0
0

Assume c Kc = 0. Then,
1

(w{ )
h
,x

h 2
dx + ( w
{ ) dx = 0

(*)

So, wh (x) = 0, for all x [0, 1], which means that cA = 0, A = 1, , n. Therefore, c = 0.
It is unnecessary to use the boundary condition wh(1) = 0, as since l is positive, the
second term of (*) leads to wh = 0.
vi.

a (u u h , w h ) + (u u h , w h ) = 0
"wh Vh
a (u u h , g ) + (u u h , g ) = (u u h , y ) = u ( y ) u h ( y )

However, since g Vh for the linear basis functions,

u( x A ) u h ( x A ) 0
The solution is not nodally exact.
vii.
u h ( x) = c1 e px + c 2 e px
which must satisfy the conditions,
u h ( x1e ) = d 1e = c1 exp( px1e ) + c 2 exp( px1e )
u h ( x 2e ) = d 2e = c1 exp( px 2e ) + c 2 exp( px 2e )
write the above equations in matrix form,
exp( px1e ) exp( px1e ) c1 d 1e

= e
e
e
exp( px 2 ) exp( px 2 ) c 2 d 2
Solve for the constant cs

d 1e exp( px1e ) d 2e exp( px 2e )

c1
exp(2 px1e ) exp(2 px 2e )

c = d e exp p ( x e + 2 x e ) + d e exp p(2 x e + x e )

1
1
2
2
1
2
2

e
e
px
px
exp(
2
)
exp(
2
)

1
2

We have
u h ( x) = d 1e N 1 ( x) + d 2e N 2 ( x)
where
exp( px1e ) exp( px) exp p( x1e + 2 x 2e ) exp( px)
N 1 ( x) =
exp(2 px1e ) exp(2 px 2e )
exp( px 2e ) exp( px) + exp p(2 x1e + x 2e ) exp( px)
N 2 ( x) =
exp(2 px1e ) exp(2 px 2e )
If we can show g Vh when y is a nodal point, the finite element solution is nodally
exact. (See vi.)

ME235A Finite Element Anlysis

Fall, 2001
c e px + c 2 e px 0 x y
g ( x; y ) = 1 px
px
y x 1
c 3 e + c 4 e
where the cs are determined from the boundary conditions as
e py
c1 = c 2 =
p 1

e py (1 + e py )
c3 =
( p 1)(e 2 py e 2 p )
e p ( y 2 ) (1 + e 2 py )
c4 =
( p 1)(e 2 py e 2 p )
Now we can show that g(x) can be represented as a linear combination of the basis
functions N1 and N2, i.e.,
e py px
(e + e px ) = AN 1 ( x) + BN 2 ( x)
g 1 ( x) =
p 1

g 2 ( x) =

e py (1 + e py )
e p ( y 2 ) (1 + e 2 py ) px
px
e

e = CN 1 ( x) + DN 2 ( x)
( p 1)(e 2 py e 2 p )
( p 1)(e 2 py e 2 p )

where
e py (e 3 px1 + e px2 )(e 2 px1 e 2 px2 )
A=
( p 1)(e 4 px1 e p ( x1 + 3 x2 ) )
e py (e px1 + e px2 )(1 + e 2 px2 )
B=
( p 1)(e 2 px1 + e 2 px2 + e p ( x1 + x2 ) )
e 2 py (e 2 px1 e 2 px2 )(e 3 px1 + e p ( 3 x1 + y ) + e p ( 2 + x2 + y ) + e p ( 2 + x2 + 3 y )
C=
( p 1)(e 4 px1 e p ( x1 + 3 x2 ) )(e 2 py e 2 p )
e 2 py (e px1 + e px2 )(e 2 px2 + e p ( 2 + y ) + e p ( 2 x2 + y ) + e p ( 2 + 3 y ) )
D=
( p 1)(e 2 px1 + e 2 px2 + e p ( x1 + x2 ) )(e 2 py e 2 p )
so that, if y is a nodal point, g Vh , and the finite element solution is exact at the
nodes.
u ( xae ) u h ( x ae ) = 0
Section 1.16 (page 49) (The problem is not restated.)
a. i. Assume u H2 is a solution of (S). Then, since u (1) = 0 and u,x (1) = 0, u S. For
any function w V,
1

w(EIu

, xxxx

f )dx = 0

Integrating by parts twice, and using the prescribed moment and shear boundary
conditions and that w (1) = 0, w,x (1) = 0,
1

Fall, 2001
1

0

for all w V. Therefore, u is a solution of (W).

ii. Assume u is a solution of (W). Since u S, u (1) = 0 and u,x (1) = 0.
1

, xx

EIu , xx dx = wfdx w, x (0) M + w(0)Q

0

Integrating by parts twice, and using the fact that w (1) = 0 and w,x (1) = 0,
1

0 = w, x EIu , xxx dx wfdx + w, x (0) M w(0)Q w, x (0) EIu , xx

1

= w( EIu , xxxx f )dx + w, x (0)( M EIu , xx (0)) w(0)(Q EIu , xxx (0))
0

Take w = ( EIu , xxxx f ) , where f is smooth, f(x) > 0 for x W, and f(1) = f,x(1) =
f(0) = f,x(0) = 0. Then,
1

0 = ( EIu , xxxx f ) 2 dx
14243
0
0

Since f > 0 on W,
EIu,xxxx = f
on W
Now, since in general, w(0) 0 and w,x(0) 0, we have
EIu xx (0) = M
natural boundary conditions
EIu , xxx (0) = Q
Therefore, u is a solution of (S).
b.
w h ( x) = c1 + c 2 x + c 3 x 2 + c 4 x 3
which must satisfy
w h ( x1 ) = c1 + c 2 x1 + c 3 x12 + c 4 x13

w h ( x 2 ) = c1 + c 2 x 2 + c 3 x 22 + c 4 x 23
w,hx ( x1 ) = c 2 + 2c 3 x1 + 3c 4 x12
w,hx ( x 2 ) = c 2 + 2c 3 x 2 + 3c 4 x 22

These conditions can be written as

1 x1 x12
x13 c1 w h ( x1 )

2
x 23 c 2 w h ( x 2 )
1 x 2 x 2
=
0 1 2 x1 3 x12 c 3 w,hx ( x1 )

h
2
0 1 2 x 2 3 x 2 c 4 w, 2 ( x 2 )
Solving for the cs, we get

ME235A Finite Element Anlysis

Fall, 2001

x12 ( x1 3x 2 )
x1 x 22
x12 x 2
(3x1 x 2 ) x 22
h
h
h
h

w
x
w
x
w
x
w
x
(
)
(
)
(
)
(
)

1
2
,x
1
,x
2
h3
h3
h2
h2
c1
x (2 x1 + x 2 )
x1 ( x1 + 2 x 2 )
6x x
6x x
h
c w h ( x1 ) 1 2 w h ( x 2 ) 1 2 + w,hx ( x1 ) 2
+
w
x
(
)
,
2
x

h3
h3
h2
h2
2 =

x1 + 2 x 2
3( x1 + x 2 )
3( x1 + x 2 )
2 x1 + x 2
c 3
h
h
h
h

w
x
w
x
w
x
w
x
(
)
(
)
(
)
(
)

1
2
,x
1
,x
2

h2
h2
h3
h3
c 4
2
2
1
1

w h ( x1 ) 3 w h ( x 2 ) 3 + w,hx ( x1 ) 2 + w,hx ( x 2 ) 2

h
h
h
h
Now, we have
w h ( x) = N 1 ( x) w h ( x1 ) + N 3 ( x) w h ( x 2 ) + N 2 ( x) w,hx ( x1 ) + N 4 ( x) w,hx ( x 2 )
where

2 3 ( x x 2 ) 2 [h + 2( x x1 )]
x =
h3
h3
h3
h3
h3
x1 x 22 x 2 (2 x1 + x 2 )
x1 + 2 x 2 2 1 3 ( x x1 )( x x 2 ) 2
N 2 ( x) = 2 +
x
x + 2 x =
h
h2
h2
h
h2
x 2 ( x 3x ) 6 x x
3( x1 + x 2 ) 2 2 3 ( x x1 ) 2 [h 2( x x 2 )]
N 3 ( x) = 1 1 3 2 13 2 x +
x 3 x =
h
h
h3
h
h3
x12 x 2 x1 ( x1 + 2 x 2 )
2 x1 + x 2 2 1 3 ( x x1 ) 2 ( x x 2 )
N 4 ( x) = 2 +
x
x + 2 x =
h
h2
h2
h
h2
N 1 ( x) =

(3x1 x 2 ) x 22

6 x1 x 2

3( x1 + x 2 )

x2 +

ME235A Finite Element Anlysis

Fall, 2001
Element shape functions
1

N1e

N2e

x1

x2

1
N3

x1

N4e

0
x1

x2

x1

For N1e and N3e

xA-1

xA

xA+1

xA-1

x2

xA

xA+1

x2